167k views
3 votes
Let g(x)=6-2x then g(0)=

Simple functions

User Mommermi
by
5.1k points

2 Answers

3 votes

Given :


\tt g(x)=6-2x

To Find :


\tt g(0)= ?

Solution :


\tt g(x)=6-2x


\tt By \: putting \: x = 0


\tt \implies g(0)=6-2(0)


\tt \implies g(0)=6 - 0


\tt \implies g(0)= 6


\pink{\tt \therefore \: value \: of \: g(0)= 6}

User Kelvin Mariano
by
5.5k points
4 votes

Answer:


g(x) = 6 - 2x \\ g(0) = 6 - 2(0) \\ \boxed {g(0) = 6}

g(0)=6 is the right answer.

User Eflles
by
4.5k points